Optimizing Digital Literacy through Microsoft Office Word Training for Elementary School Students in Sukajati Village - Salsa Fatikhah (Konsultan Jurnal Ilmiah Indonesia, 2025)
In the digital era, mastery of word processing software has become a fundamental competency required from an early age to support academic and future career readiness. However, access to information technology training in rural areas is often limited. This article aims to describe the implementation of a Microsoft Office Word training program for sixth-grade students at Sukahati Elementary School in Sukajati Village. The method used was an intensive mentoring approach, encompassing theoretical presentations, practical demonstrations, and evaluation using the N-gain score. The results showed a significant increase in student understanding, with an N-gain score of 56.15%, categorized as